Carbon capture technology outdoor fabric and preparation method thereof

By using carbon capture polyester yarn in outdoor fabrics and combining the bio-based TPU film, the problem of insufficient waterproof, breathable and antistatic properties of existing fabrics is solved, and the excellent performance and environmentally friendly characteristics of the fabric are achieved.

CN119820950AActive Publication Date: 2025-04-15GAOFAN (ZHEJIANG) INFORMATION TECH CO LTD

Patent Information

Application Number
CN202510092253.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-15
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Existing outdoor fabrics have shortcomings in waterproof, breathable and antistatic properties, especially polyester fibers and DuPont Sorona bio-based fibers are prone to static electricity, and have poor breathability and moisture-absorbing and sweating properties.

Method used

The base fabric is obtained by blending carbon capture polyester yarn with DuPont Sorona bio-based fiber, and a bio-based TPU film is combined on one side of the base fabric. Carbon capture polyester fiber is prepared by melt blending process, and binary metal oxides and additives are added to improve antistatic properties.

Benefits of technology

It achieves excellent waterproof performance, good moisture permeability and significantly improved antistatic properties of the fabric, meets the needs of outdoor sports and has good environmental protection significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820950A_ABST
    Figure CN119820950A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon capture technology outdoor fabric and a preparation method thereof, and relates to the technical field of fabric preparation, the carbon capture technology outdoor fabric comprises a base cloth and a bio-based TPU film compounded on one side of the base cloth, the base cloth is obtained by weaving carbon capture polyester yarns as warp yarns and carbon capture polyester fiber-Dupont Sorona bio-based fiber blended yarns as weft yarns; the carbon capture polyester yarn comprises, by mass, 90%-95% of carbon capture polyester chips and 5%-10% of antistatic master batches, and the antistatic master batches comprise binary metal oxide, polyethylene glycol, maleic anhydride and auxiliaries according to the mass ratio of (2-5): 10: 1: 1. According to the fabric, the materials are all environmentally friendly, the defect that a traditional polyester fabric is prone to static electricity is overcome, meanwhile, the fabric can meet the waterproof, breathable and moisture-permeable requirements of outdoor sports, and the fabric has good outdoor performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fabric preparation, and specifically relates to a carbon capture technology outdoor fabric and a preparation method thereof. Background Art

[0002] Carbon dioxide capture and storage (CCS) is one of the important ways to achieve greenhouse gas emission reduction and has good development prospects. CCS technology refers to the process of separating carbon dioxide from the source of industry or related energy, transporting it to a storage site, and isolating it from the atmosphere for a long time. It includes three technical links: carbon capture, carbon transportation, and carbon storage. Carbon dioxide captured from integrated refining and chemical industries is liquefied, purified, hydrogenated, and other steps to obtain green methanol. Green methanol is used as a raw material to further produce green ethylene glycol. Green ethylene glycol and terephthalic acid are used as polymerization monomers to form long-chain polymers through polymerization reactions, namely polyethylene terephthalate (commonly known as polyester PET). The preparation technology roadmap is as follows: Figure 1 As shown. Carbon capture polyester PET is a downstream technical product of CCS technology. Carbon capture polyester PET is consistent with conventional polyester PET. Both can be used in the textile field to obtain polyester fibers through spinning technology. The captured carbon dioxide is used as a raw material to produce fibers, which has a good environmental protection prospect.

[0003] Sugar is extracted from plants, and the product BIO-PDO is obtained after fermentation. A suitable catalyst is selected to polymerize BIO-PDO with a polymer compound (PTA, PTT, etc.) to obtain a multifunctional fiber with environmentally friendly materials, namely DuPont Sorona bio-based fiber. The fiber has better wrinkle recovery, stretch recovery, dimensional stability, stronger air permeability, moisture absorption and perspiration wicking, and blending with polyester fiber can improve the shortcomings of poor air permeability and non-perspiration of polyester fiber, and thus can be better applied to the field of outdoor fabrics. However, both polyester fiber and DuPont Sorona bio-based fiber have the disadvantage of being easy to generate static electricity. In order to better improve the application performance of the two, it is also necessary to improve the antistatic ability of the fabrics prepared by the two. In addition, for outdoor fabrics, it is also necessary to meet certain waterproof properties and air permeability and moisture permeability. In this regard, the present invention proposes a carbon capture technology outdoor fabric and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a carbon capture technology outdoor fabric and a preparation method thereof in order to solve the above problems.

[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0006] As a first aspect of the present invention, the present invention provides a carbon capture technology outdoor fabric, including a base fabric and a bio-based TPU film composited on one side of the base fabric, wherein the base fabric is woven with carbon capture polyester yarn as warp yarn and blended yarn prepared from carbon capture polyester fiber and DuPont Sorona bio-based fiber as weft yarn;

[0007] The carbon capture polyester yarn comprises 90-95% of carbon capture polyester chips and 5-10% of antistatic masterbatch in terms of mass percentage. The antistatic masterbatch comprises binary metal oxide, polyethylene glycol, maleic anhydride and additives in a mass ratio of (2-5):10:1:1.

[0008] As a further optimization solution of the present invention, the fiber composition of the fabric includes 60-75% carbon capture polyester fiber and 25-40% DuPont Sorona bio-based fiber in terms of mass percentage.

[0009] As a further optimization scheme of the present invention, the binary metal oxide includes nickel molybdate, cobalt molybdate or nickel cobaltate.

[0010] As a further optimization scheme of the present invention, the bio-based TPU film comprises, by mass percentage, 80-90% of bio-based TPU particles, 5-10% of ethylene-vinyl acetate copolymer, 1-5% of nano calcium carbonate and 1-5% of germanium stone powder.

[0011] As a further optimization scheme of the present invention, the auxiliary agent includes a phosphate coupling agent, a hindered phenol antioxidant 1010 and polyvinyl pyrrolidone.

[0012] As a second aspect of the present invention, the present invention also provides a method for preparing the carbon capture technology fabric as described above, which specifically comprises the following steps:

[0013] (1) firstly, carbon capture PET polyester chips and antistatic masterbatch are melt blended to obtain carbon capture polyester fibers, then, the carbon capture polyester fibers are spun to obtain carbon capture polyester yarns, and finally, the carbon capture polyester fibers are blended with DuPont Sorona bio-based fibers to obtain carbon capture polyester fibers-DuPont Sorona bio-based fiber blended yarns;

[0014] (2) using carbon capture polyester yarn as warp yarn and carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn as weft yarn to obtain a base fabric;

[0015] (3) The base fabric obtained in step (2) is glued and online cast and laminated on a casting machine to form a bio-based TPU film, thereby obtaining the carbon capture technology outdoor fabric.

[0016] As a further optimization scheme of the present invention, the preparation method of the carbon capture polyester yarn in step (1) is specifically as follows: carbon capture PET polyester chips and antistatic masterbatch are melt blended, extruded through a spinneret assembly, cooled by annular air, bundled and oiled, drawn, heat set and wound to obtain carbon capture polyester fibers, and then the carbon capture polyester fibers are subjected to the steps of cleaning, carding, drawing, roving, spinning and winding to obtain carbon capture polyester yarn.

[0017] As a further optimization scheme of the present invention, the weaving density of the warp yarn in step (2) is 50-70 strands / inch, the weaving density of the weft yarn is 45-60 strands / inch, and the weaving structure of the base cloth is plain weave.

[0018] The beneficial effects of the present invention are:

[0019] (1) The materials used in the present invention are all environmentally friendly. The coating component of the fabric is a bio-based TPU film, and the fiber component of the fabric is a carbon capture polyester fiber and a DuPont Sorona bio-based fiber. The carbon capture polyester fiber and the DuPont Sorona bio-based fiber respectively use carbon capture technology and bio-based environmental protection technology, which have good environmental protection significance.

[0020] (2) The water repellency level of the fabric developed by the present invention can reach level 4, the hydrostatic pressure resistance value can reach more than 9000mmH2O, and the moisture permeability can reach 9000g / (m 2 ·24h) or more, which can meet the requirements of outdoor sports and give the fabric better outdoor performance.

[0021] (3) The carbon capture polyester yarn provided by the present invention includes carbon capture polyester chips and antistatic masterbatch, and binary metal oxides are introduced into the composition of the antistatic masterbatch. By virtue of the conductive properties of the binary metal oxides, the disadvantage of the traditional polyester yarn that it is easy to generate static electricity is overcome, thereby enabling the fabric to have excellent antistatic properties and good comprehensive performance.

[0022] (4) The bio-based TPU film provided by the present invention has a certain antistatic ability and excellent mechanical properties. When combined with a base fabric, it can further improve the antistatic performance and comprehensive performance of the fabric. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A technical roadmap for the preparation of carbon capture polyester PET. DETAILED DESCRIPTION

[0024] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0025] 1. Materials and Methods

[0026] In the following examples, any method not specified may be carried out according to conventional methods, and other materials, reagents, etc. used may be obtained through commercial channels unless otherwise specified.

[0027] In the following embodiments, the preparation method of the carbon capture polyester yarn is to melt blend the carbon capture polyester chips and the antistatic masterbatch, extruded through the spinneret assembly, cooled by annular blowing, bundled and oiled, drawn, heat set and wound to obtain the carbon capture polyester fiber, and then the carbon capture polyester fiber is made into a carbon capture polyester yarn with a fineness of 50 to 100D by the steps of cleaning, carding, drawing, roving, spun yarn and winding. The melt blending process conditions are generally adjusted according to the selection of raw materials, etc. In the following embodiments, the melt blending process conditions are uniformly selected as follows: the melt blending spinning temperature is 270°C, the annular blowing wind temperature is 25°C, the annular blowing wind speed is 0.4m / min, the stretching multiple is 2.4 times, the stretching temperature is 140°C, the heat setting temperature is 130°C, and the winding speed is 4000m / min.

[0028] In the following embodiments, the preparation method of the antistatic polyester masterbatch is as follows: the required raw materials are added to a high-speed mixer with a rotation speed of 1500 rpm, mixed at a mixing temperature of 180°C for 20 minutes, and then the mixed materials are added to a twin-screw extruder for melt blending, the melt temperature is controlled at 300°C, the screw speed is 300 rpm, and the twin-screw extruder is sheared and mixed for 15 minutes, and then extruded, cooled, pelletized, and dried.

[0029] In the following embodiments, the carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarns are all made of carbon capture polyester fiber and DuPont Sorona bio-based fiber as raw materials, spun using a ring spinning machine, the blending mass ratio is preferably 4:1, and the fineness is also 50-100D.

[0030] In the following embodiments, the process of compounding the bio-based TPU film on one side of the base fabric is as follows: first, the raw materials of the bio-based TPU film are mixed and then added to a twin-screw extruder for melt extrusion, the feed port temperature of the twin-screw extruder is 140-150°C, the temperature of the first zone is 160-170°C, the temperature of the second zone is 170-180°C, the temperature of the third zone is 190-195°C, the temperature of the fourth zone is 190-195°C, and the head temperature is 185-190°C. Subsequently, the bio-based TPU pellets are obtained by pelletizing using a pelletizer, and then the base fabric is coated with PU glue using a coating machine, and the bio-based TPU pellets and the glued base fabric are cast and laminated online on a casting machine to form a bio-based TPU film, and the thickness of the bio-based TPU film is 0.1 mm. 2. Specific embodiments

[0032] Example 1

[0033] The carbon capture technology outdoor fabric provided in this embodiment comprises, by weight percentage, 60% carbon capture polyester fiber and 40% DuPont Sorona bio-based fiber.

[0034] The specific structure includes a base fabric and a bio-based TPU film composited on one side of the base fabric. The base fabric is woven with carbon capture polyester yarn as the warp yarn and carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn as the weft yarn; the specifications of the carbon capture polyester yarn and the carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn are both 50D / 12F.

[0035] The carbon capture polyester yarn comprises 90% carbon capture polyester chips and 10% antistatic masterbatch in terms of mass percentage. The antistatic masterbatch comprises nickel molybdate, polyethylene glycol, maleic anhydride and additives in a mass ratio of 5:10:1:1. The additives are selected from phosphate coupling agent, hindered phenol antioxidant 1010 and polyvinyl pyrrolidone.

[0036] The bio-based TPU film comprises, by weight percentage, 80% of bio-based TPU particles, 10% of ethylene-vinyl acetate copolymer, 5% of nano calcium carbonate and 5% of germanium stone powder.

[0037] The preparation method is as follows: first, carbon capture PET polyester chips and antistatic masterbatch are melt blended to obtain carbon capture polyester fiber, then, the carbon capture polyester fiber is spun to obtain carbon capture polyester yarn, and finally, the carbon capture polyester yarn is blended with DuPont Sorona bio-based yarn to obtain carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn, and then the carbon capture polyester yarn is used as the warp yarn and the carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn is used as the weft yarn to weave the base fabric, the weaving density of the warp yarn is 50 strands / inch, the weft yarn is 60 strands / inch, and the weaving structure of the base fabric is plain weave. Finally, the base fabric is glued, and the bio-based TPU film is cast online on the casting machine to obtain the carbon capture technology outdoor fabric.

[0038] Example 2

[0039] The carbon capture technology outdoor fabric provided in this embodiment comprises, by weight percentage, 75% carbon capture polyester fiber and 25% DuPont Sorona bio-based fiber.

[0040] The specific structure includes a base fabric and a bio-based TPU film composited on one side of the base fabric. The base fabric is woven with carbon capture polyester yarn as the warp yarn and carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn as the weft yarn; the specifications of the carbon capture polyester yarn and the carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn are both 100D / 12F.

[0041] The carbon capture polyester yarn comprises 95% carbon capture polyester chips and 5% antistatic masterbatch in terms of mass percentage. The antistatic masterbatch comprises cobalt molybdate, polyethylene glycol, maleic anhydride and additives in a mass ratio of 2:10:1:1. The additives are selected from phosphate coupling agent, hindered phenol antioxidant 1010 and polyvinyl pyrrolidone.

[0042] The bio-based TPU film comprises, by weight percentage, 90% of bio-based TPU particles, 5% of ethylene-vinyl acetate copolymer, 2% of nano calcium carbonate and 3% of germanium stone powder.

[0043] In the method for preparing the fabric, except that the weaving density of the warp yarn is 70 yarns / inch and the weaving density of the weft yarn is 45 yarns / inch, the remaining steps are the same as those in Example 1.

[0044] Example 3

[0045] The carbon capture technology outdoor fabric provided in this embodiment comprises, by weight percentage, 70% carbon capture polyester fiber and 30% DuPont Sorona bio-based fiber.

[0046] The specific structure includes a base fabric and a bio-based TPU film composited on one side of the base fabric. The base fabric is woven with carbon capture polyester yarn as the warp yarn and carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn as the weft yarn; the specifications of the carbon capture polyester yarn and the carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn are both 50D / 12F.

[0047] The carbon capture polyester yarn comprises 95% carbon capture polyester chips and 5% antistatic masterbatch in terms of mass percentage. The antistatic masterbatch comprises nickel cobaltate, polyethylene glycol, maleic anhydride and additives in a mass ratio of 2:10:1:1. The additives are selected from phosphate coupling agent, hindered phenol antioxidant 1010 and polyvinyl pyrrolidone.

[0048] The bio-based TPU film comprises, by weight percentage, 85% of bio-based TPU particles, 10% of ethylene-vinyl acetate copolymer, 3% of nano calcium carbonate and 2% of germanium stone powder.

[0049] In the method for preparing the fabric, except that the weaving density of the warp yarn is 70 yarns / inch and the weaving density of the weft yarn is 50 yarns / inch, the remaining steps are the same as those in Example 1.

[0050] The fabrics prepared in Examples 1-3 were subjected to the following wearing performance tests.

[0051] (1) Water repellency test: The test was conducted according to ISO 4920:2012 "Determination of the resistance of textile fabrics to water splashing". In addition, a commercially available 100% wool fabric (yarn count of 80, yarn twist of 1000 twists / m, S twist) was used as a control group and subjected to the same test treatment as above.

[0052] The test method is to spray the sample with distilled or deionized water. The sample is mounted on a retaining ring and placed at a 45° angle to the horizontal plane, with the center of the sample located below the nozzle. The water level is assessed by comparing the appearance of the sample with the assessment criteria and pictures. The levels range from 0 to 5, where 0-both sides of the sample are completely wetted; 1-the entire surface of the sprayed surface is wetted; 2-half of the sprayed surface is wetted; 3-only a small discontinuous area of ​​the sprayed surface is wetted; 4-the sprayed surface is not wetted, but there are small water droplets on the sprayed surface; 5-the sprayed surface is not wetted, and there are no small water droplets on the sprayed surface. Level 5 indicates the best waterproof performance.

[0053] (2) Hydrostatic pressure resistance test: The fabric was subjected to a hydrostatic pressure resistance test in accordance with GB / T 4744-2013. The test method is as follows: Wipe off the experimental water on the clamping surface, clamp the sample, and make the front of the sample contact the water. Apply a continuously increasing water pressure to the sample at a water pressure increase rate of 60cm H2O / min, and observe the water seepage phenomenon. During the pressure increase process, stop increasing the pressure when the third water droplet appears on the sample, and record the hydrostatic pressure value at this time.

[0054] (3) Moisture permeability test: According to the national standard GB / T12704.1-2009 (a), the moisture permeability of the sample was tested using the FX3180 moisture permeability measuring instrument. During the test, the temperature was 38°C, the humidity was 90.0%, the air flow rate was 0.5m / s, and the test area was 28.27cm 2 Before the test, the test chamber needs to be pre-humidified. After the automatic humidity adjustment is completed, the instrument starts the moisture permeability test and automatically records the moisture permeability data once every hour, twice in total. After the experiment is completed, the moisture permeability data of the sample is manually recorded, and the average of 5 groups of experimental data for each group of samples is used as the final data.

[0055] A fabric sample made of 100% polyester fiber and composited with a bio-based TPU film on one side (the composition of the bio-based TPU film is the same as that of Example 1) was used as control group 1 and subjected to the same test as above.

[0056] The test results are shown in Table 1.

[0057] Table 1. Fabric wearing performance test results

[0058]

[0059]

[0060] It can be seen from Table 1 that the fabrics prepared in Examples 1-3 all have excellent waterproof and moisture permeability, which is slightly better than that of the control group. The water repellency level of the fabrics prepared in Examples 1-3 can reach level 4, the hydrostatic pressure resistance value reaches more than 9000 mmH2O, and the moisture permeability reaches 9000 g / (m 2 ·24h) or more, which can meet the requirements of outdoor sports and give the fabric better outdoor performance.

[0061] Since both carbon capture polyester yarn and DuPont Sorona bio-based yarn have the disadvantage of being prone to generating static electricity, the present invention optimizes the composition of the carbon capture polyester yarn as follows, and adjusts the composition of the antistatic masterbatch according to Table 2.

[0062] Table 2. Composition of antistatic masterbatch

[0063]

[0064] In Table 2, the additives selected for each group are phosphate coupling agent, hindered phenol antioxidant 1010 and polyvinyl pyrrolidone.

[0065] According to the composition of the antistatic masterbatch given in Table 2, fabric AF was prepared on the basis of the remaining preparation steps and conditions being the same as those in Example 1. A fabric containing 100% polyester fiber was used as control group 2.

[0066] The fabrics of Example 1, fabrics AF, and fabrics of control groups 1-2 were tested for antistatic properties according to GB / T 12703.1-2021 "Textiles-Test methods for electrostatic properties Part 1: Corona charging method", and the electrostatic voltage half-life was used as the test index (excellent: half-life ≤10s; good: 10<half-life ≤30; general: 30<half-life ≤60; poor:>60s).

[0067] The results are shown in Table 3.

[0068] Table 3. Test results of fabric antistatic properties

[0069]

[0070]

[0071] It can be seen from Table 3 that by adjusting the composition of the antistatic masterbatch, the fabric can obtain better antistatic ability. By comparing Example 1 with fabric A, it can be seen that the degree of improvement in the antistatic performance of the fabric is proportional to the amount of binary metal oxide added. By comparing Example 1 with fabric BC, it can be seen that when binary metal oxides are selected from nickel molybdate, cobalt molybdate, and nickel cobaltate, the antistatic performance of the fabric is improved. By comparing Example 1 with fabric DE, it can be seen that the effect of monometallic oxides on improving the antistatic performance of the fabric is not as good as that of binary metal oxides. By comparing control group 1 with control group 2, it can be seen that the bio-based TPU film provided by the present invention also has a positive effect on improving the antistatic performance of the fabric.

[0072] In order to further explore the influence of the composition of the bio-based TPU film on the performance of the fabric, based on the raw material ratio of the bio-based TPU film given in Example 1, the composition of the bio-based TPU film was adjusted according to Table 4.

[0073] Table 4. Composition of bio-based TPU films

[0074]

[0075] According to the composition of the bio-based TPU film given in Table 2, a bio-based TPU film ae was prepared. The bio-based TPU film ae was compounded on one side of a fabric composed of 100% polyester fiber according to the above-mentioned laminating method to prepare a test fabric ae, and a fabric composed of 100% polyester fiber without lamination was used as a blank control group.

[0076] Fabric ae and blank control were tested for antistatic performance according to GB / T 12703.1-2021 "Textiles-Test methods for electrostatic properties Part 1: Corona charging method", and the static voltage half-life was used as the test index (excellent: half-life ≤ 10s; good: 10 < half-life ≤ 30; general: 30 < half-life ≤ 60; poor: > 60s). The results are shown in Table 5.

[0077] Table 5. Test results of fabric antistatic properties

[0078]

[0079] It can be seen from Table 5 that, compared with fabric a and fabric b, the addition of germanium stone powder can improve the antistatic ability of the fabric to a certain extent. Compared with fabric a and fabric c, the difference between the two is that nano calcium carbonate is omitted in the composition of the bio-based TPU film of fabric c. From the results, it can be seen that it has a negative impact on the antistatic ability of the fabric.

[0080] Comparing fabric a and fabric d, it can be seen that omitting germanium stone powder corresponds to increasing the amount of ethylene-vinyl acetate copolymer, which has a negative impact on the antistatic ability of the fabric. Comparing fabric a and fabric e, it can be seen that germanium stone powder has the effect of improving the antistatic ability of the fabric compared with traditional inorganic filler talc.

[0081] Furthermore, the mechanical properties of the bio-based TPU film ae were measured according to GB / T 528-1998 standard. The test temperature was 23°C, the chuck spacing was 64 mm, and the upper and lower chucks were separated at a rate of 500 mm / min. The tensile strength, elongation at break and tear strength of the bio-based TPU film ae were measured. The average of 5 groups of experimental data was used as the final data for each group of samples. The results are shown in Table 6.

[0082] Table 6. Mechanical properties test results of bio-based TPU films

[0083]

[0084]

[0085] From Table 6, it can be seen that compared with bio-based TPU film e, the addition of germanium powder in the composition of bio-based TPU film has a positive effect on improving the mechanical properties of the film. Compared with bio-based TPU film a, bio-based TPU film b is different in that the germanium powder is omitted and the amount of nano-calcium carbonate is increased. From the results, it can be seen that the mechanical properties of bio-based TPU film b have decreased. Compared with bio-based TPU film a, the difference between bio-based TPU film c and bio-based TPU film a is that the amount of nano-calcium carbonate is omitted and the amount of nano-calcium carbonate is increased. From the results, it can be seen that the mechanical properties of bio-based TPU film c have decreased significantly. The introduction of appropriate amounts of nano-calcium carbonate, ethylene-vinyl acetate copolymer and germanium powder forms a stable organic-inorganic compatible system, which has a positive significance for improving the deficiencies in the mechanical properties of bio-based TPU particles.

[0086] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

Claims

1. A carbon capture technology outdoor fabric, characterized by: It comprises a base fabric and a bio-based TPU film compounded on one side of the base fabric, wherein the base fabric is woven by using carbon capture polyester yarn as warp yarn and blended yarn prepared from carbon capture polyester fiber and DuPont Sorona bio-based fiber as weft yarn; The carbon capture polyester yarn comprises 90-95% of carbon capture polyester chips and 5-10% of antistatic masterbatch in terms of mass percentage. The antistatic masterbatch comprises binary metal oxide, polyethylene glycol, maleic anhydride and additives in a mass ratio of (2-5):10:1:

1.

2. The carbon capture technology outdoor fabric according to claim 1, characterized in that: The fiber composition of the fabric includes 60-75% carbon capture polyester fiber and 25-40% DuPont Sorona bio-based fiber in terms of mass percentage.

3. The carbon capture technology outdoor fabric according to claim 1, characterized in that: The binary metal oxide includes nickel molybdate, cobalt molybdate or nickel cobaltate.

4. The carbon capture technology outdoor fabric according to claim 1, characterized in that: The bio-based TPU film comprises, by mass percentage, 80-90% of bio-based TPU particles, 5-10% of ethylene-vinyl acetate copolymer, 1-5% of nano calcium carbonate and 1-5% of germanium stone powder.

5. The carbon capture technology outdoor fabric according to claim 1, characterized in that: The auxiliary agents include a phosphate coupling agent, a hindered phenol antioxidant 1010 and polyvinyl pyrrolidone.

6. A method for preparing the carbon capture technology outdoor fabric according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) firstly, carbon capture PET polyester chips and antistatic masterbatch are melt blended to obtain carbon capture polyester fibers, then, the carbon capture polyester fibers are spun to obtain carbon capture polyester yarns, and finally, the carbon capture polyester fibers are blended with DuPont Sorona bio-based fibers to obtain carbon capture polyester fibers-DuPont Sorona bio-based fiber blended yarns; (2) using carbon capture polyester yarn as warp yarn and carbon capture polyester fiber-DuPont Sorona bio-based fiber blended yarn as weft yarn to obtain a base fabric; (3) The base fabric obtained in step (2) is glued and online cast and laminated on a casting machine to form a bio-based TPU film, thereby obtaining the carbon capture technology outdoor fabric.

7. The method for preparing a carbon capture technology outdoor fabric according to claim 6, characterized in that: The preparation method of the carbon capture polyester yarn in step (1) is specifically as follows: carbon capture polyester chips and antistatic masterbatch are melt blended, extruded through a spinneret assembly, cooled by annular air blowing, bundled and oiled, drawn, heat-set and wound to obtain carbon capture polyester fibers, and then the carbon capture polyester fibers are subjected to the steps of cleaning, carding, drawing, roving, spinning and winding to obtain carbon capture polyester yarn.

8. The method for preparing a carbon capture technology outdoor fabric according to claim 6, characterized in that: In step (2), the weaving density of the warp yarn is 50-70 yarns / inch, the weaving density of the weft yarn is 45-60 yarns / inch, and the weaving structure of the base fabric is plain weave.

Citation Information

Patent Citations

  • Method for preparing internal vehicular decorative material with functions of eliminating harmful gases and releasing anions

    CN105751641A

  • Antistatic fabric and preparation method thereof

    CN112779660A

  • Polyester fiber excellent in antistatic performance and its production

    JP1994057535A

  • Carbon dioxide capturing material

    JP2012024648A

  • knitted fabric generating high heat for sweat suit and Manufacturing method thereof

    KR102290332B1

Cited By

  • Carbon capture profiled polyester staple fiber and preparation method thereof

    CN121451319A